2012
DOI: 10.1016/j.brainres.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus ambiguus cholinergic neurons activated by acupuncture: Relation to enkephalin

Abstract: Acupuncture regulates autonomic function. Our previous studies have shown that electroacupuncture (EA) at the Jianshi–Neiguan acupoints (P5–P6, underlying the median nerve) inhibits central sympathetic outflow and attenuates excitatory cardiovascular reflexes, in part, through an opioid mechanism. It is unknown if EA at these acupoints influences the parasympathetic system. Thus, using c-Fos expression, we examined activation of nucleus ambiguus (NAmb) neurons by EA, their relation to cholinergic (preganglioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…On the other hand, opioids released during EA inhibited cardiopulmonaryinduced activation of parasympathetic outflow. We recently have shown that preganglionic cholinergic NAmb neurons activated with acupuncture are located in close proximity to enkephalinergic fibers (13). Although in this anatomical study we were unable to determine whether the EA-activated cholinergic (preganglionic) neurons were of cardiac origin (13), enkephalin is known to be present in fibers in close proximity to cardiac vagal neurons in the NAmb (4,48).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, opioids released during EA inhibited cardiopulmonaryinduced activation of parasympathetic outflow. We recently have shown that preganglionic cholinergic NAmb neurons activated with acupuncture are located in close proximity to enkephalinergic fibers (13). Although in this anatomical study we were unable to determine whether the EA-activated cholinergic (preganglionic) neurons were of cardiac origin (13), enkephalin is known to be present in fibers in close proximity to cardiac vagal neurons in the NAmb (4,48).…”
Section: Discussionmentioning
confidence: 97%
“…Enkephalin microinjected into the NAmb in contrast decreases HR (1). Additionally, we recently have shown that cholinergic preganglionic parasympathetic neurons in the NAmb activated by EA are situated in close proximity to fibers containing enkephalin, suggesting the potential for interaction (13). These studies suggest that modulation of NAmb neuronal activity by EA may reduce PBGinduced bradycardia and cardiac vagal-evoked activity in the NAmb, possibly through an opioid or a GABAergic mechanism.…”
mentioning
confidence: 94%
“…In this regard, we recently have shown that this region participates in gastric distention-induced bradycardia associated with hypercapnia and respiratory acidosis (39). EA at P5-P6 acupoints activates NAmb neurons in close proximity to enkephalinergic processes, implying that EA exerts at least part of its cardiovascular actions through this nucleus and that enkephalin participates in EA processing in this region (13). Furthermore, we observed that EA at the P5-P6 acupoints inhibited evoked neuronal discharge in the NAmb during vagal afferent fiber stimulation (41), an action that was attenuated by blockade of GABA A receptors with gabazine.…”
Section: Discussionmentioning
confidence: 99%
“…Zhao et al [42] recently suggested that acupuncture at HT7, but not at PC6, reduces alcohol withdrawal effects through increasing TH mRNA and protein expression in the VTA and NAc, respectively, along with dopamine levels in the NAc. However, stimulation of PC6 can effectively treat Internet addiction [43] and alleviate the withdrawal syndrome of heroin addiction [44]; the acupoint is also involved in neurotransmitter regulation [45]. It seems compatible with the above description; ST36 has also been reported to influence opioid-induced addiction and side effects; however ST36 was not effective on the current METH study with no reports of the cocaine studies [46].…”
Section: Discussionmentioning
confidence: 66%